Visual Packaging and Perceived Emotional Value: A Study on Islamic Branded Cosmetics - Prabowo, Desny Sekartanti Putri; Aji, Hendy Mustiko (UI Scholars Hub, 2021)
Research Aims: This study aims to examine the effect of visual packaging and perceived emotional value on purchase intention of Islamic-branded cosmetics. Design/Methodology/Approach: The data were collected from an online survey of selected respondents. By using the purposive sampling technique, the respondents were limited to those who knew of or have used Islamic-branded cosmetics. The data were analysed using the PLS-SEM method. Research Findings: Altogether, this study's sample comprised 257 respondents and found that visual packaging of Islamic-branded cosmetics positively affects perceived emotional value and attitude. However, the results also indicate that visual packaging exerts no significant effect on purchase intention. Moreover, this study also found that perceived emotional value and attitude strongly affected consumers' purchase intention with Islamic-branded cosmetics. Theoretical Contribution/Originality: Most studies on halal or Islamic-branded cosmetics have focussed on religiosity, ingredients and safety, but little attention has been paid to packaging. Therefore, this study contributes to the literature by examining visual packaging's effect on perceived emotional value, attitudes and purchase intention. Managerial Implications in the Southeast Asian Context: Managers of Islamic-branded cosmetics in Indonesia should consider developing strategies to make their packaging visually attractive. The managers also are encouraged to focus on creating emotional value in Islamic-branded cosmetics packaging. Research Limitations and Implications: This study has a limitation in terms of questionnaire distribution. Most of the respondents in this study are students under 20 years old, and most are from Java island.